2018
DOI: 10.1158/1078-0432.ccr-18-0551
|View full text |Cite
|
Sign up to set email alerts
|

Brain Development and Heart Function after Systemic Single-Agent Chemotherapy in a Mouse Model of Childhood Leukemia Treatment

Abstract: Multiple ALL chemotherapy agents can affect postnatal brain development or heart function. This study provides a ranking of agents based on potential toxicity, and thus highlights a subset likely to cause side effects in early adulthood for further study.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…The evidence regarding the impact of treatment burden on neurocognitive outcomes is conflicting, with some studies showing significant associations between exposure to MTX or corticosteroids, 28,29 while other studies did not 8,30 . The lack of association between cumulative treatment exposures and school performance observed in the present study may be due to difficulties detecting the individual contributions of agents that were administered in a combination and via various routes 8,28,31 …”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The evidence regarding the impact of treatment burden on neurocognitive outcomes is conflicting, with some studies showing significant associations between exposure to MTX or corticosteroids, 28,29 while other studies did not 8,30 . The lack of association between cumulative treatment exposures and school performance observed in the present study may be due to difficulties detecting the individual contributions of agents that were administered in a combination and via various routes 8,28,31 …”
Section: Discussioncontrasting
confidence: 73%
“…8,30 The lack of association between cumulative treatment exposures and school performance observed in the present study may be due to difficulties detecting the individual contributions of agents that were administered in a combination and via various routes. 8,28,31 Younger age at diagnosis has commonly been found to be associated with poorer neurocognitive outcomes following childhood…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical models may provide an important alternative approach to investigating these factors and candidate mechanisms. We have already employed this strategy to examine the influence of cranial radiation on brain development ( de Guzman et al, 2015 , de Guzman et al, 2019 , Beera et al, 2018 ), including detailed comparisons to human outcomes ( Nieman et al, 2015 ), and for systematic evaluation of ALL chemotherapy agents and their contribution to brain toxicity ( Spencer Noakes et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The delayed appearance of PRV‐ir cells in the neocortex compared to CR‐ir neurons (present on PN0, increase between PN5 and 10 and decline to adult levels by PN15) or SST‐ir interneurons (present at PN0 and drastically increase between PN3 and 21) may potentially render PRV interneuronal progenitors more vulnerable to the induction protocol. Systemic DOX administration in PN17 mice also causes brain volume reductions, as assessed by magnetic resonance imaging (MRI) studies, attributed to proinflammatory effects . Histopathologic findings in DLP rodent brains have shown that DOX, a cytotoxic chemotherapy drug, and LPS, a Toll‐like receptor 4 agonist, can cause prominent inflammation in the peri‐infusional cortical area .…”
Section: Discussionmentioning
confidence: 99%
“…Systemic DOX administration in PN17 mice also causes brain volume reductions, as assessed by magnetic resonance imaging (MRI) studies, attributed to proinflammatory effects. 53 Histopathologic findings in DLP rodent brains have shown that DOX, a cytotoxic chemotherapy drug, and LPS, a Toll-like receptor 4 agonist, can cause prominent inflammation in the peri-infusional cortical area. 16 Whether these inflammatory changes contribute to the bilateral reduction in PRV interneurons and cortical atrophy, for example, via leakage of cytokines in the cerebroventricular space, remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%